2010
DOI: 10.1016/j.devcel.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway Regulates Wnt/β-Catenin Signaling

Abstract: Several developmental pathways contribute to processes that regulate tissue growth and organ size. The Hippo pathway has emerged as one such critical regulator. However, how Hippo signaling is integrated with other pathways to coordinate these processes remains unclear. Here, we show that the Hippo pathway restricts Wnt/beta-Catenin signaling by promoting an interaction between TAZ and DVL in the cytoplasm. TAZ inhibits the CK1delta/epsilon-mediated phosphorylation of DVL, thereby inhibiting Wnt/beta-Catenin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
450
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 519 publications
(474 citation statements)
references
References 52 publications
18
450
4
2
Order By: Relevance
“…Hippo pathway cross-talks with other signaling pathways to orchestrate cell-fate decisions was lately reinforced in studies outlining the connection of Hippo components with the PI(3)K-mTOR pathway, Wnt/β-catenin pathway, and mechanotransduction. [33][34][35] Our findings that active c-Abl functions as a switcher between different transcriptional programs might explain its tumor suppressor function. It was reported that c-Abl counteracts TGF-β-mediated transformation and EMT, 16 but the underlying mechanism was unclear.…”
Section: Discussionmentioning
confidence: 83%
“…Hippo pathway cross-talks with other signaling pathways to orchestrate cell-fate decisions was lately reinforced in studies outlining the connection of Hippo components with the PI(3)K-mTOR pathway, Wnt/β-catenin pathway, and mechanotransduction. [33][34][35] Our findings that active c-Abl functions as a switcher between different transcriptional programs might explain its tumor suppressor function. It was reported that c-Abl counteracts TGF-β-mediated transformation and EMT, 16 but the underlying mechanism was unclear.…”
Section: Discussionmentioning
confidence: 83%
“…Accordingly, abrogation of TAZ levels enhances Wnt-stimulated Dvl phosphorylation, followed by b-catenin-mediated gene transcription in the nucleus. 55 Inhibition of canonical Wnt signaling might result in activation of non-canonical JNK signaling (see below for details), as shown in several studies. 56,57 NON-CANONICAL WNT PATHWAY Non-canonical Wnt signaling activities include Wnt/JNK/PCP pathway and Wnt/Ca 2+ pathway.…”
Section: Canonical Wnt Pathwaymentioning
confidence: 92%
“…The Yorkie homolog TAZ binds to Dishevelled in the cytoplasm 81 . This interaction inhibits Dishevelled function, leading to reduced β-catenin signalling upon Wnt stimulation.…”
Section: Bountiful Crosstalk In the Hippo Pathwaymentioning
confidence: 99%
“…Conversely, loss of TAZ enhances β-catenin signaling. This cross-talk is conserved in Drosophila, as loss of Yorkie in flies also enhanced Wingless (Wg) target expression in vivo 81 . Similarly, some of the progrowth, anti-apoptotic functions of the PI3K/Akt/PKB pathway were recently found to be due to phosphorylation of Mst1, providing another point of integration between known growth factor pathways and Hippo activity 82 .…”
Section: Bountiful Crosstalk In the Hippo Pathwaymentioning
confidence: 99%